Design, synthesis and biological activity of pyrazinamide derivatives for anti-Mycobacterium tuberculosis - Shiyang Zhou; Shanbin Yang; Gangliang Huang (Taylor & Francis Group, 2017)
A total of 11 pyrazinamide derivatives were designed and synthesised using pyrazinamide as the lead compound, which was optimised by structural modification with alkyl chains, six-membered rings, and bioisosterism, respectively. The target compounds were synthesised using pyrazinecarboxylic acid as the starting material by acylation, amidation, and alkylation, respectively. Their structures were confirmed by 1H NMR, 13C NMR, HRESIMS, and elemental analysis, respectively. The bioactivities of derivatives were assayed using bacteriostatic experiment and minimum inhibitory concentration experiment. It was showed that the derivatives had good inhibitory effect on Mycobacterium tuberculosis. The biological activity of derivative 1f was the best among all compounds, its antibacterial activity was 99.6%, and the minimum inhibitory concentration was 8.0 µg/mL.